Teacher's pest - Gilman, Charles; Smith, Eugene (Illustrator) (Philadelphia : Quirk Books, 2013)
"DON'T BE FOOLED by his friendly smile, his perfect manners, or his shiny red apple. Student council president Howard Mergler is actually a sinister bug-monster in disguise and he's summoning swarms of roaches, wasps, fleas, and head lice into the corridors of Lovecraft Middle School! Twelve-year-old Robert Arthur is the only student who can stop him--but he'll need help from his best friends: the school bully, the school ghost, and an extremely courageous two-headed rat."--Amazon.com.
Keywords: Middle schools -- Juvenile fiction; Monsters -- Juvenile fiction; Teachers -- Juvenile fiction; Middle schools -- Fiction; Monsters -- Fiction; Teachers -- Fiction; Middle schools; Monsters; Teachers; Fiction; Juvenile works